"A lot better than it used to be": a qualitative study of adolescents' dynamic social recovery capital. (4th March 2023) - Jurinsky, Jordan; Cowie, Kiefer; Blyth, Sophia; Hennessy, Emily A.
Abstract: Background: Substance use recovery is a dynamic process for youth, and social networks are tied to the recovery process. The Recovery Capital for Adolescents Model (RCAM) situates the resources accessible through social networks – social recovery capital (SRC) – in a larger framework of developmentally-informed recovery resources. This study aims to investigate the social network experiences among recovering youth enrolled in a recovery high school to understand how social influences help to build, or act as barriers to building, recovery capital. Methods: To gain insight into these networks, Social Identity Maps and semi-structured interviews were conducted with ten youth ages 17–19 years (80% male; 50% non-Hispanic White). Study visits were conducted virtually, recorded, transcribed, and thematically analyzed using the RCAM as an organizing framework. Results: Results supported that adolescent social networks play a unique and multifaceted role in the recovery journey. Three key nuances emerged: change permeates adolescent networks throughout the treatment and recovery process; shared substance use history and non-stigmatizing attitudes play a key role in connecting with others; and SRC is interconnected with human, financial, and community recovery capital. Conclusions: With adolescent recovery receiving increased attention from policy makers, practitioners, and researchers, the RCAM may be a useful way to contextualize available resources. Findings suggest SRC as a crucial, yet complex component intertwined with all other forms of recovery capital.